2019
DOI: 10.12788/jhm.3308
|View full text |Cite
|
Sign up to set email alerts
|

An On‐Treatment Analysis of the MARQUIS Study: Interventions to Improve Inpatient Medication Reconciliation

Abstract: It is unclear which medication reconciliation interventions are most effective at reducing inpatient medication discrepancies. Five United States hospitals’ interdisciplinary quality improvement (QI) teams were virtually mentored by QI-trained physicians. Sites implemented one to seven evidence-based interventions in 791 patients during the 25-month implementation period. Three interventions were associated with significant decreases in potentially harmful discrepancy rates: (1) defining clinical roles and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…A hospital-based educational program found an increase in knowledge and self-e cacy for proper medication reconciliation from pre-and post-surveys (16). Improving knowledge is important and may improve the quality of medication lists gathered through medication reconciliation, but the effect on outcomes is less clear (17)(18)(19). Similar to our ndings, others have found that providing education alone is not enough to guarantee consistently accurate medication reconciliation (17)(18)(19).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A hospital-based educational program found an increase in knowledge and self-e cacy for proper medication reconciliation from pre-and post-surveys (16). Improving knowledge is important and may improve the quality of medication lists gathered through medication reconciliation, but the effect on outcomes is less clear (17)(18)(19). Similar to our ndings, others have found that providing education alone is not enough to guarantee consistently accurate medication reconciliation (17)(18)(19).…”
Section: Discussionsupporting
confidence: 65%
“…Improving knowledge is important and may improve the quality of medication lists gathered through medication reconciliation, but the effect on outcomes is less clear (17)(18)(19). Similar to our ndings, others have found that providing education alone is not enough to guarantee consistently accurate medication reconciliation (17)(18)(19). Additionally, a previous study conducted by our group identi ed numerous barriers to medication reconciliation including lack of time, lack of patient knowledge, and lack of a standardized work ow (4).…”
Section: Discussionmentioning
confidence: 99%
“…26 Prior studies have shown that pharmacy-driven medication reconciliation processes and patient counseling at discharge can reduce unintentional medication discrepancies and preventable ADEs. [27][28][29] Site 3's reduction in unintentional medication discrepancies after hiring an inpatient clinical pharmacist and implementing a pharmacy-driven discharge-medication reconciliation and counseling process reinforces the importance of this type of intervention. Site 2's results differed from those in a prior study in which unintentional medication discrepancies were reduced after implementing pharmacy technicians to obtain admission medication histories.…”
Section: Discussionmentioning
confidence: 93%
“…For example, compared with nurses and pharmacists, physicians tend to prioritise other tasks in a resource-constrained setting 26. Therefore, it is crucial for organisational leaders to identify local champions, sponsor human factors evaluations and identify dedicated personnel (eg, pharmacy technicians) based on clinic resources and characteristics 8 19 49…”
Section: Discussionmentioning
confidence: 99%